A systematic literature review on overconfidence and related biases Influencing Investment Decision Making - Karki, Uttam (Economic and business review, 2024)
n the current market scenario, it has been observed that biases are among the most significant factors influencing investment decisions. Among these biases, overconfidence is a common phenomenon managers tend to exhibit while making decisions. To understand the role of overconfidence bias in investment decision making, this study thoroughly scrutinizes and consolidates the current research on overconfidence bias. To achieve the objective, this study performs a systematic review of literature utilizing the PRISMA approach and examines 92 journal articles published in the last 20 years. Results suggest that the other two biases—hindsight and confirmation—are related to overconfidence bias. In addi- tion, the review suggests that biases result in three major outcomes. The first, positive, aspect pertains to the promotion of mental well-being and significant allocation to research and development investments. Conversely, the second, negative, aspect involves the manipulation of operating cash flow, which tends to diminish the value of shareholders. Third, there is a preference for internal financing over external financing options. Furthermore, the research also suggests factors that may overcome the influence of the overconfidence bias. This study demonstrates its originality through thematic analysis, which effectively examines multiple dimensions of biases. Moreover, incorporating these research findings can enhance managerial decision-making processes, promote more objective assessments, and ultimately improve the overall quality of investment choices.
Keywords: decision making; enterprises; investicije; investments; literature review; odločanje; podjetje; pregled literature